Cost Effectiveness of ‘On Demand’ Hiv Pre-Exposure Prophylaxis for Non-Injection Drug-Using Men Who Have Sex with Men in Canada - Estelle Ouellet; Madeleine Durand; Jason R Guertin; Jacques LeLorier; Cécile L Tremblay (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Recent trials report the efficacy of continuous tenofovir-based pre-exposure prophylaxis (PrEP) for prevention of HIV infection. The cost effectiveness of ‘on demand’ PrEP for non-injection drug-using men who have sex with men at high risk of HIV acquisition has not been evaluated.